Mastering the magnetic susceptibility of magnetically responsive bicelles with 3β-amino-5-cholestene and complexed lanthanide ions. Issue 17 (12th April 2017) - Isabettini, Stéphane; Liebi, Marianne; Kohlbrecher, Joachim; Ishikawa, Takashi; Fischer, Peter; Windhab, Erich J.; Walde, Peter; Kuster, Simon
Abstract : Generating lanthanide-chelating aminocholesterol-doped phospholipid bicelles with unprecedented magnetic alignment and tunable magnetic susceptibility. Abstract : The magnetic susceptibility of lanthanide-chelating bicelles was selectively enhanced by introducing 3β-amino-5-cholestene (aminocholesterol, Chol-NH2 ) in the bilayer. Unprecedented magnetic alignment of the bicelles was achieved without altering their size. An aminocholesterol conjugate (Chol-C2 OC2 -NH2 ), in combination with different lanthanide ions, offers the possibility of fine-tuning the bicelle's magnetic susceptibility.